ANALISIS KINERJA SIMPANG TIGA MENGGUNAKAN APLIKASI PROGRAM aaSIDRA 2.0 DAN TRANSYT 11.1 (Studi Kasus : Simpang Tiga Bersinyal dan Bundaran Kartasura) - , WILDI KUSUMASARI, Prof. Ir. Sigit Priyanto, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Urban transportation problems have been developing complexly. The majority urban traffic problems occured at intersection. The problems that occur at both signalised intersection and roundabout in Kartasura are a long queue during peak hours and peak days in every week, month, or special occasions such as Lebaran. Based on the intersections problems, the objectives of this research is to analyze the existing problems that occur on both intersections such as geometric conditions and traffic characteristics, analyze the intersections performance include intersection capacity, degree of saturation, and delay using MKJI 1997and aaSIDRA 2.0, and find the optimum solution to intersections using aaSIDRA 2.0 and TRANSYT. The object of the research are both signalised intersection and roundabout at Kartasura where located only 150 meters and strategically located at the meeting point between Surakarta, Semarang, and Yogyakarta. Research was conducted by analyzing the existing conditions of the two intersections with the MKJI 1997 method and inputing the data into aaSIDRA and TRANSYT software. And the final step is to choose the best scenario of all three methods (MKJI 1997, aaSIDRA, and TRANSYT) to each intersection and then make it as reference to make solute the intersections problems. The results showed that the existing condition of a signalized intersection having problems, which have a degree of saturation is 1.012. While the existing condition of the roundabout is still pretty good because degree of saturation is still worth 0.690. Based on the analysis of both intersection scenario, it can be seen that the best scenario for a signalized intersection is the result of analysis using aaSIDRA which can raise the performance of the intersection so that the value of saturation degree be 0.709 and the value of delay is 14.7 sec/pcu. While the best scenario for the roundabout is the result of analysis using MKJI 1997 at the existing condition which degree of saturation is 0.690 and the value of delay is 6.58 sec/pcu. Intersection analysis using TRANSYT by installing a signal at roundabout and coordinate two intersections was resulted worse performance if it compared with uncoordinated intersections performance.